Excited State Properties of Oligophenyl and Oligothienyl Swivel Cruciforms - Pina, J. (2008)
A comprehensive study has been undertaken of the electronic spectral and photophysical properties of two oligophenyl (BPH and BPHF) and one oligothienyl (BTF) swivel cruciforms involving measurements of absorption, fluorescence, and phosphorescence spectra, quantum yields of fluorescence (phiF), phosphorescence (phiPh) and triplet formation (phiT), lifetimes of fluorescence (τF) and of the triplet state (τT), and quantum yields of singlet oxygen production (phiΔ). From these, all radiative kF and radiationless rate constants, kIC and kISC, have been obtained in solution. The energies of the lowest lying singlet and triplet excited states were also determined at 293 K. Several of the above properties have also been obtained at low temperature and in the solid state (thin films). In general, for the phenyl oligophenyl (BPH) and for the oligothienyl (BTF) compounds, the radiationless decay channels (phiIC + phiISC) are the dominant pathway for the excited-state deactivation, whereas with the fluorene based oligophenyl BPHF the radiative route prevails. In contrast to the general rule found for related oligomers (and polymers) where radiative emission from T1 is absent, with the compounds studied, phosphorescence has been observed for all of the compounds, indicating that this type of functionalization can lead to emissive triplets. Time-resolved fluorescence decays with picosecond resolution revealed multiexponential (bi- and triexponential) decay laws compatible with the existence of more than one species or conformation in the excited state. These results are discussed on the basis of conformational flexibility in the excited state.